Comparative Study on Mechanical Strength Properties of Concrete by Using Demolished Concrete Waste - K, Sabarinathan; R, Ashwathi (International Research Journal of Multidisciplinary Technovation, 2019)
The growing environmental awareness and Construction waste, is increasing day by day which in turn makes the world in seeking for examining the characteristics of Construction waste and obtaining a solution by using its reliable segments such that it can be used as a raw material and Conservation the natural recourses like Coarse aggregate